DETECTION OF BIOACTIVE CHEMICAL COMPOUNDS IN THE METHANOLIC EXTRACT OF AZOLLA FILICULOIDES LAMARK FERN BY GC-MS TECHNIQUE - Alkhafaji, Haneen H K; Altameme, Huda J M; Alsharifi, Saif M H (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The phytochemical analysis of Azolla filiculoides Lamark in the methanolic whole plant extract was undertaken and published for the first time in Iraq in this article. The existence of twenty-four bioactive phytochemical compounds were discovered using GC-MS analysis. , such as Ethyl Formate, 1,3-Cyclohexanedione, Butanal, 2-Nonenal,9-Octadecenal,2,4,6-Trimethyl-1-nonene, 3-(Prop-2-enoyloxy) tetradecane, Carbonic acid, 9-Oxabicyclo [6.1.0] nonane. Oleic Acid, 13-Docosenoic acid, Z-10-Pentadecen-1-ol, Oxirane, Diethyl carbonate. Hydroperoxide, 2-Butene ozonide. These various active phytochemicals of alkenes, alkanes, esters, ethers, and carboxylic acids were found in the plant with great potential to bind with other compounds, this plant is great to be used as a filter to waste water.